SPIRITUAL EDUCATION IN ISLAMIC EDUCATION: A CONCEPTUAL STUDY OF TARBAWI HADITHS - Maslani, Maslani; Hakim, Dede Arif Rahman Nur; Kartika, Yuni; Wardana, Vikki (Jurnal Konseling Pendidikan Islam, 2025)
Spiritual education is a crucial aspect of Islam for shaping noble character through the cultivation of emotions and feelings. This article aims to examine the concept of spiritual education in Islam based on Tarbawi hadiths and to elaborate on its implementation for learners. This study employs a descriptive analysis method of relevant hadiths, such as those addressing anger management, guarding the heart from envy (hasad), and dealing with sadness and disappointment. The analysis results indicate that spiritual education supports self-control, the development of noble character, and the cultivation of positive attitudes in facing life’s challenges. The implementation of spiritual education for learners involves the habituation of worship, emotional regulation, and the formation of balanced character in their relationship with Allah (hablum minallah) and with fellow humans (hablum minannas). This study underscores the importance of spiritual education in creating individuals who are resilient spiritually, emotionally, and socially.